Editorial: Highlights in Pediatric Pain 2021/2022. - Onyeka, Tonia C.; De la Vega, Rocío; Fisher, Emma; Finley, G. Allen (My University, 2023)
Chronic pain affects one in four children and adolescents and has been declared a global health priority because of its economic burden to society and substantial impact on child and family. Psychological treatments have been found to be effective in reducing pain intensity and disability, however, there is considerable variability in treatment response, such that some children and adolescents benefit while others do not and more research has been called for in this area. This editorial highlights the broad diversity of research performed across the Pediatric Pain section, including a summary of pediatric chronic pain management modalities, from bench to bedside, and an intersect of the biopsychosocial aspects of pain. It includes five manuscripts: three original studies, one brief research report and one mini review. The review article by Jotwani et al. highlights the importance of behavioural treatments in pediatric chronic pain, the latter being widespread and of complex nature as a result of the progressive growth of the nervous system. The authors found mixed efficacy of psychological interventions for pain outcomes, proposing interactions between psychosocial factors such as pain catastrophizing and biobehavioral mechanisms like inflammatory biomarkers, and the relevance of such interactions to patient treatment outcomes, the authors posit that in order to further expand this vital research area, conducting mechanistic clinical trials (which are studies involving human participants to have a better understanding of biologic or behavioral mechanisms) utilizing mixed methods may help explain the mixed results. They suggest that neuroimaging techniques (especially fNIRs imaging) to observe for neurologic pain processes and artificial intelligence to detect pain predictors are new frontiers in mechanistic pediatric pain research.
Keywords: Dolor - Aspectos psicológicos; Pediatría; COVID-19; Pediatric pain; Pain mechanisms; Pain treatment; Biomarkers; Risk factors; Cognitive behavioral therapy (CBT)